Modeling and Analysis of Pitch Angle Control on Variable Speed Wind Turbines - Percin, Hasan Bektas; Calıskan, Abuzer (My University, 2021)
Nowadays, due to the increasing demand for electrical energy, investments in renewable energies are a satisfactory solution to meet this demand. Wind energy, which is one of these renewable energies, has many advantages such as low environmental impact, renewable structure, and decreasing system costs with developing technology. However, the instant changes of the wind, affect the sustainability of the system and the production efficiency negatively. Maximum efficiency, stable and long-lasting operation is aimed at wind energy conversion systems with permanent magnet synchronous generators (PMSG). In line with these objectives, systems should be used with appropriate control structures. Modeling studies in the computer environment allow analyzing the different controls to be used in energy conversion, which can be difficult and costly to work on the real system. These studies provide analysis, comparison of various control parameters, and adjustments before system installation, Thus, the problems can be prevented before the installation, higher performance and less costly designs can be achieved. In this study, the basic components and parameters of the wind energy system were explained and mathematical models of these parameters were obtained. The working principle of the control structures for the system was explained through these models. The general system modeling, which includes pitch angle control for higher wind speeds, was designed in Matlab/Simulink environment, and graphical analysis of the control structure was performed based on various system parameters. As a result, the control structure ensured stable operation of the system at higher wind speeds.
Keywords: Modeling; Matlab/Simulink; Wind energy; Pitch angle; Permanent magnet synchronous generator